Associations between special diet and incidence risk of osteoporosis: a Mendelian randomization study - Zhou, Changwen; Yang, Lixue; Liu, Ce; Ma, Hongzhong; Yang, Feng; Chen, Liheng (Frontiers in Public Health, 2024)
Introduction Osteoporosis is a prevalent challenge in clinical orthopedics, affecting a significant percentage of individuals aged 50 and above. The goal of this study was to comprehensively understand the relationships between a specialized dietary regimen and the risk of developing osteoporosis. Methods This study employed extensive genome-wide association study (GWAS) summary statistics derived from the UK Biobank. It encompassed 8 kinds of special diets and 7 datasets pertaining to osteoporosis and associated symptoms. The principal analytical approach employed was the inverse-variance weighted method. Additionally, sensitivity analysis was employed to elucidate the diverse multiplicity patterns observed in the final model. Results Our results showed that there is significant evidence that a gluten-free diet is associated with osteoporosis [odds ratio (OR): 1.080, 95% confidence interval (CI): 1.048–1.112, p = 4.23E-07)]. Furthermore, there exists a suggestive link between the three distinct dietary approaches and osteoporosis [(OR: 0.949, 95%CI: 0.929–0.970, p = 3.00E-06) for comprehensive consumption; (OR: 1.053, 95%CI: 1.018–1.089, p = 2.23E-03) for abstaining from wheat consumption; (OR: 1.036, 95%CI: 1.005–1.068, p = 1.97E-02) for abstaining from sugar consumption]. No additional correlation between the special dietary regimens and osteoporosis has been observed. Conclusion Our research has uncovered a notable correlation between a gluten-free diet and the occurrence of osteoporosis. Furthermore, it exerts a promoting influence on the onset of osteoporosis, which stands in direct contradiction to the therapeutic principles for Celiac Disease’s complications. As such, a novel association among these three elements is postulated.